Bone mineral density gains related to basketball practice in boys: Cohort study - Júnior, Mário Antônio Rodrigues [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; de Marco, Rafael Luiz [UNESP]; Ito, Igor Hideki [UNESP]; dos Santos, Marcelo Rodrigues Ribeiro [UNESP]; Fernandes, Rômulo Araújo [UNESP] (Faculdade de Filosofia e Ciências, 2017)
Introduction: In recent decades, the prevalence of osteoporosis has significantly increased, impacting in a significant manner on health care costs worldwide. Objective: To analyze the impact of basketball practice on bone mineral density of male adolescents. Methods: 9 - month cohort study carried out with 27 adolescents (controls, n = 13 [11.9 ± 2.2 years] and basketball players, n = 14 [13.4 ± 1.2 years]). Bone mineral density was measured in different body segments (upper limbs, lower limbs, spine, and total) using the dual energy X-ray absorptiometry technique. Intake of vitamin D, chronological age, somatic maturation, fat-free mass, and height were adopted as confounders. The statistical analysis was composed of the Student's t-test, analysis of covariance, and Pearson/partial correlations. Results: Regardless of confounders, there was a positive relationship between higher basketball practice time and bone density gains in the upper limbs (r = 0487 [95%CI = 0.131 to 0.732]). Conclusion: The practice of basketball seems to affect bone mineral density gains in adolescents, mainly when the practice is prolonged.
Keywords: Adolescent medicine; Basketball; Bone density; Sports medicine